All the King’s Horses: Stable Administration in New Kingdom Egypt - Litecky, Tessa Genevieve David (AUC Knowledge Fountain, 2021)
Horses were an important part of Egyptian society during the New Kingdom as tools of warfare, status symbols of the elite, and an emblem of the power of kingship. However, little is known about how these animals were trained and cared for, or who was working in horse stables and their roles. There are no texts or images that explicitly explain methods of horse management. Therefore, this topic has been generally overlooked in the literature. This thesis combines two threads of evidence to create a more complete picture of the organization, purpose, and function of horse stables and the treatment of horses. First, this work identifies and examines the surviving evidence from archeological, textual, and artistic sources relating to horse stables and horse care. Particular attention is given to the limited archaeological remain of horse stables in Egypt, texts that speak to the duties of Stable Masters and grooms, and depictions of interaction between handlers and grooms, feeding, as well as images of natural horse behaviors. In addition, examples of horse stables and management from neighboring contemporary cultures are surveyed to identify potential parallels. Then, the titles of people associated with horse stables from the 18th, 19th, and 20th Dynasties are analyzed to better understand how the hierarchy, roles, and titles changed throughout the New Kingdom and explain the development of horse care and training. This study concludes that the size of complexity of the stable administration expanded significantly from the 18th to the 19th Dynasty. In the 19th and 20th Dynasties, the position of Stable Master became more numerous with a greater variety of roles and responsibilities. In contrast, the role of Overseer of Horses transitioned from a practical position to one that was largely ceremonial. Furthermore, this thesis maintains that horse stables were present in a variety of contexts, including private, royal, military, and mobile military camps. However, horse management activities were not restricted only to the stables. It is likely that chariot horses were sometimes kept in pastures or with their charioteers during times of peace. This study also argues that breeding operations took place outside the stables, likely in the Delta.